2021
DOI: 10.5056/jnm20151
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Clinical Evaluation and Formation Mechanism of Irritable Bowel Syndrome-like Symptoms in Inflammatory Bowel Disease Patients in Remission

Abstract: Background/AimsSome inflammatory bowel disease (IBD) patients in remission suffer from irritable bowel syndrome (IBS)-like symptoms (IBD-IBS). The pathogenesis has not yet been elucidated. The study aim is to evaluate relationships among quality of life (QOL), psychological status, and visceral sensitivity, and explore the formation mechanism of IBD-IBS. MethodsForty-seven patients with Crohn's disease in remission, 24 ulcerative colitis in remission, 26 IBS, and 20 healthy controls were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…A smaller study, enrolling 47 patients with CD and 24 with UC in clinical remission, demonstrated a prevalence of Rome III IBS-like symptoms in 29.8% and 50.0% of patients, respectively. 30 As observed in our cohort, quality of life scores were lower, and anxiety or depression scores higher, in patients with IBS-type symptoms than those without. However, the authors did not evaluate fluctuations in, or stability of, these scores over time.…”
Section: Ta B L Esupporting
confidence: 77%
See 1 more Smart Citation
“…A smaller study, enrolling 47 patients with CD and 24 with UC in clinical remission, demonstrated a prevalence of Rome III IBS-like symptoms in 29.8% and 50.0% of patients, respectively. 30 As observed in our cohort, quality of life scores were lower, and anxiety or depression scores higher, in patients with IBS-type symptoms than those without. However, the authors did not evaluate fluctuations in, or stability of, these scores over time.…”
Section: Ta B L Esupporting
confidence: 77%
“…However, in our study, which recruited patients with IBD in clinical remission, patients with IBD with IBS‐type symptoms had higher anxiety or depression scores compared to those without IBS‐type symptoms at baseline and multiple other time points. A smaller study, enrolling 47 patients with CD and 24 with UC in clinical remission, demonstrated a prevalence of Rome III IBS‐like symptoms in 29.8% and 50.0% of patients, respectively 30 . As observed in our cohort, quality of life scores were lower, and anxiety or depression scores higher, in patients with IBS‐type symptoms than those without.…”
Section: Discussionsupporting
confidence: 56%
“…According to previous evidence collected in both human and animals, visceral pain is correlated with an augmented activity of MCs through the intestine [ 14 , 26 ]. In the post-inflammatory phase of colitis induced by DNBS, an increased density of MCs has been detected in the submucosa with respect of controls ( p < 0.01), accompanying pain persistence.…”
Section: Resultsmentioning
confidence: 99%
“…Gut inflammation represents a major risk factor for the development of the persistent visceral hypersensitivity that underlies the onset of pain and altered motility and that often persists after the resolution of intestinal damage [ 2 ]. It is particularly evident in patients affected by inflammatory bowel diseases (IBDs), who continue suffering from abdominal pain and discomfort even after achieving clinical remission, developing a post-inflammatory irritable bowel syndrome (PI-IBS) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The broad range of beneficial effects shown by Brassicaceae constituents, such as the glucosinolates (GSLs) [ 9 , 10 ], raised our interest in studying the potential of employing these plants in the therapy for gastrointestinal pain. Indeed, the main derivatives of GSL hydrolysis, isothiocyanates (ITCs), have been reported to modulate both inflammatory processes and oxidative stress [ 10 , 11 ], two factors contributing to the development of chronic pain in patients [ 3 , 6 , 12 , 13 ]. ITCs also display a prebiotic activity [ 12 , 13 , 14 ] that is highly relevant in the context of gut pain [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%